Analysis of The Advantages of Microsoft Teams as A Corporate Communication Tool in Supporting Employee Performance - Melati, Ria (Green Publisher Indonesia, 2025)
This study aims to evaluate the advantages of Microsoft Teams' features as a corporate communication tool that supports employee performance. The research methodology includes literature analysis and a Systematic Literature Review (SLR). Through SLR, this study collects, reviews, synthesizes, and summarizes various relevant studies on the topic. The research process begins with searching for related articles using the Publish or Perish application, which accesses the Scopus database with the keyword